Gambaran Dukungan Caregiver terhadap Kepatuhan Minum Obat Pasien Skizofrenia di Puskesmas Denpasar Selatan - Kadek Ary Surya Putra Wibawa; Putu Aryani; Komang Ayu Kartika Sari; Putu Cintya Denny Yuliyatni (Pusat riset dan Inovasi Nasional, 2026)
Schizophrenia is a chronic mental disorder that requires long-term medication adherence to prevent relapse and improve patients’ quality of life. Caregivers play a crucial role in encouraging medication adherence through emotional, informational, instrumental, and supervisory support. This descriptive quantitative study with a cross-sectional design aimed to describe caregiver support and medication adherence among schizophrenia patients at the South Denpasar Public Health Center. A total of 100 respondents, who were family members or caregivers of schizophrenia patients, were selected using a consecutive sampling technique. Data were collected through structured interviews using questionnaires and analyzed descriptively. The results showed that most caregivers provided good support (63%), particularly in accompanying patients during medication intake, actively interacting with them, and following health workers’ recommendations. Furthermore, patients’ medication adherence was mostly in the moderate (45%) and good (35%) categories. These findings indicate that caregiver support plays a significant role in improving medication adherence among schizophrenia patients. Strengthening caregiver knowledge and optimizing health education by healthcare workers are essential to further enhance adherence.